Story of Nagbiegu, appellation of Naa Abudu - Lunna, Abubakari; Locke, David (Tufts Archival Research Center, 2005)
Told by Abubakari Lunna on March 2 and 6, 2001. Edited by David Locke. Describes the origins of the Nagbiegu rhythm, which is played for the chief Naa Abudu.